Comparison of Influence of Blood Pressure and Carotid-Femoral Pulse Wave Velocity on Target Organ Damage in Hypertension - Chao, Huijuan; He, Yan; Wang, Qian; Bai, Yaya; Avolio, Alberto; Deng, Xueqin; Zuo, Junli (Frontiers in Cardiovascular Medicine, 2022)
Objectives：Assessment of target organ damage (TOD) is an important part of the diagnosis and evaluation of hypertension. Carotid-femoral pulse wave velocity（cf-PWV) is considered to be the gold-standard for noninvasive arterial stiffness assessment. This study aims to analyze the risk of TOD in people with different phenotypes of peripheral blood pressure and cf-PWV. Methods：The study cohort was recruited from December 2017 to September 2021 at Ruijin Hospital in Shanghai. It was divided into 4 groups according to peripheral blood pressure (pBP) and cf-PWV. TOD was assessed as carotid intima-media thickness (CIMT), chronic kidney disease (CKD), urinary albumin-creatinine ratio (ACR), estimated glomerular filtration rate (eGFR) and left ventricular mass index (LVMI). Results：A total of 1257 subjects (mean age 53.13 ± 12.65 years, 64.2% males) was recruited. Age, body mass index (BMI) and fasting blood glucose (FBG), as well as peripheral systolic blood pressure (pSBP), peripheral diastolic blood pressure (pDBP), peripheral pulse pressure (pPP) were significantly different in the four groups (P<0.01). eGFR, ACR, LVMI and CIMT were significantly different among different groups (P<0.01). The risk of ACR abnormality was significantly higher in the group with elevated pBP (P=0.005, OR 2.264, 95%CI 1.277-4.016; and in the group with elevated pBP and cf-PWV (P=0.003, OR 1.482, 95%CI 1.144-1.920), while left ventricular hypertrophy (LVH) was significantly higher in the group with elevated cf-PWV (P=0.002, OR 1.868, 95%CI 1.249-2.793). Conclusion：Different profiles based on the status of PBP and cf-PWV associated with different TOD. Individuals with higher pBP have an increased risk of ACR abnormality, while individuals with only cf-PWV elevated have a higher risk of LVH.